Capacity‐constrained entrepreneurs and their product portfolio size: The response to a platform design change on a Chinese sharing economy platform. (11th August 2020) - Tae, C. Jennifer; Luo, Xueming; Lin, Zhijie
Abstract: Research summary: How do entrepreneurs on a sharing economy platform (SEP) with a limit to aggregate output (capacity constraints) respond to a platform design change emphasizing buyer feedback? Not all supply‐side complementors can diversify or scale their offerings. Focusing on those who can change the former, but not the latter, we examine how entrepreneurs change their product portfolio size after the platform design changed to emphasize buyer feedback. We found that their product portfolio size decreased following the change, and more so for those with more positive feedback. While the sales increased for entrepreneurs after the change, buyer feedback deteriorated. Our results show how SEPs in emerging economies can foster entrepreneurship and elucidate the importance of nonscale‐free resources of supply‐side entrepreneurs to better understand platform dynamics. Managerial summary: Do sellers change the number of products on offer when the app owner rewards sellers with high user ratings? While research has examined how sellers adjust the number of products to get high ratings, little attention has been paid to sellers with capacity constraints. This is problematic, as sellers on sharing economy apps often have a limit on the total quantity of products they can produce. Using data from a Chinese home cooked meal selling app, we show that sellers decreased the number of products they sell when the app owner began to reward high user ratings. The decrease was more pronounced for sellers with higher ratings. As a result, sales revenue increased, but user ratings decreased. Implications for practitioners and policymakers are discussed within.